Role of adipocyte Na,K-ATPase oxidant amplification loop in cognitive decline and neurodegeneration - Komal Sodhi; Rebecca Pratt; Xiaoliang Wang; Hari Vishal Lakhani; Sneha S. Pillai; Mishghan Zehra; Jiayan Wang; Lawrence Grover; Brandon Henderson; James Denvir; Jiang Liu; Sandrine Pierre; et al. (iScience, 2021)
Summary: Recent studies suggest that a western diet may contribute to clinical neurodegeneration and dementia. Adipocyte-specific expression of the Na,K-ATPase signaling antagonist, NaKtide, ameliorates the pathophysiological consequences of murine experimental obesity and renal failure. In this study, we found that a western diet produced systemic oxidant stress along with evidence of activation of Na,K-ATPase signaling within both murine brain and peripheral tissues. We also noted this diet caused increases in circulating inflammatory cytokines as well as behavioral, and brain biochemical changes consistent with neurodegeneration. Adipocyte specific NaKtide affected by a doxycycline on/off expression system ameliorated all of these diet effects. These data suggest that a western diet produces cognitive decline and neurodegeneration through augmented Na,K-ATPase signaling and that antagonism of this pathway in adipocytes ameliorates the pathophysiology. If this observation is confirmed in humans, the adipocyte Na,K-ATPase may serve as a clinical target in the therapy of neurodegenerative disorders.